Quality of osmotically dehydrated melon in sucrose solutions with addition of acids - Argandoña, Eliana Janet Sanjinez; Nishiyama, Cintia; Hubinger, Míriam Dupas (Pesquisa Agropecuaria Brasileira, 2002)
The combination of osmotic dehydration and weak acids addition is a mild process that results in a final product with organoleptic characteristics very similar to fresh and "ready to eat" fruit, appropriate for immediate consumption. The purpose of this work was to evaluate the influence of citric and lactic acids on the production of osmotically dehydrated melon and on its final quality. Melon (Cucumis melo inodorus, cultivar Gold Mine) pieces of 40x30x15 mm were immersed in three types of dehydrating solutions (sucrose + citric acid, sucrose + lactic acid and control) of different concentrations (50 to 70ºBrix). Osmotic dehydration was carried out for up to three hours under controlled temperature (30 to 50ºC). The addition of acids had no significant influence on chroma parameters. However, solution concentration and process temperature increased lightness significantly. The fracture stress was weaker in processed samples as compared to fresh ones, but the fracture strain was much higher for samples treated with lactic acid at 50ºC, resulting in more viscoelastic but firmer products.